Supramolecular Packing Drives Morphological Transitions of Charged Surfactant Micelles. (18th August 2020) - Schäfer, Ken; Kolli, Hima Bindu; Killingmoe Christensen, Mikkel; Bore, Sigbjørn Løland; Diezemann, Gregor; Gauss, Jürgen; Milano, Giuseppe; Lund, Reidar; Cascella, Michele
Abstract: The shape and size of self‐assembled structures upon local organization of their molecular building blocks are hard to predict in the presence of long‐range interactions. Combining small‐angle X‐ray/neutron scattering data, theoretical modelling, and computer simulations, sodium dodecyl sulfate (SDS), over a broad range of concentrations and ionic strengths, was investigated. Computer simulations indicate that micellar shape changes are associated with different binding of the counterions. By employing a toy model based on point charges on a surface, and comparing it to experiments and simulations, it is demonstrated that the observed morphological changes are caused by symmetry breaking of the irreducible building blocks, with the formation of transient surfactant dimers mediated by the counterions that promote the stabilization of cylindrical instead of spherical micelles. The present model is of general applicability and can be extended to all systems controlled by the presence of mobile charges. Abstract : Micellar shape changes of sodium dodecyl sulfate are associated with different binding modes of the counterions. Morphological changes are caused by symmetry breaking of the irreducible building blocks, with the formation of transient surfactant dimers mediated by the counterions that promote the stabilization of cylindrical instead of spherical micelles.